The symbiotic relationship between the music culture of the Mulao yifan festival and the music culture of the Han nationality in Luocheng county - Meilin, Xie; Narantsatsral, Delgerkhuu (Mongolian Journal of Arts and Culture, 2023)
This paper mainly studies the symbiosis and integration of the music culture of the Mulao Yifan Festival and the music culture of the Han nationality from the aspects of music form, musical instrument, dance, cultural exchange and social harmony. Such research will help people understand more deeply the cultural diversity and cultural interaction among ethnic groups in Luocheng County promote the exchange, integration and inheritance of different ethnic music cultures. Луоченгийн Мулаочуудын Ифан наадмын хөгжмийн соёл ба Хан үндэстний хөгжмийн соёлд хийсэн семиотикийн харьцуулсан судалгаа